Kabbalah and modernity : interpretations, transformations, adaptations - Huss, Boaz.; Pasi, Marco.; Stuckrad, Kocku von, 1966- (Aries Book Series, 2010)
The persistence of kabbalistic groups in the twentieth century has largely been ignored or underestimated by scholars of religion. Only recently have scholars began to turn their attention to the many-facetted roles that kabbalistic doctrines and schools have played in nineteenth- and twentieth-century culture. Often, and necessarily, this new interest and openness went along with a contextualization and re-valuation of earlier scholarly approaches to kabbalah. This volume brings together leading representatives of this ongoing debate in order to break new ground for a better understanding and conceptualization of the role of kabbalah in modern religious, intellectual, and political discourse.